PEMBERDAYAAN PEKERJA SEKTOR INFORMAL DALAM MENINGKATKAN HIGIENE SANITASI MAKANAN UNTUK MENCEGAH KONTAMINASI MAKANAN DAN TIMBULNYA PENYAKIT - Nazma Izzati; Diva Nurlatifah; Fathiah Qolbu; Kevin Nicholas; M Rihan Subagja; Rifa Ajrina Faisal; Sintia Damayanti; Tya Raudotul Jannah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Food hygiene and sanitation are important factors in maintaining food safety in the informal sector snack food industry. This study aims to improve workers' knowledge and hygiene practices through an educative and empowerment approach. The methods used included direct observation, interactive counseling, and leaflet distribution to workers at Sugema Cookie Factory. The study results show that educational activities can increase workers' awareness of the importance of personal hygiene, the use of personal protective equipment, and sanitation practices in the production area. In addition, there was a positive behavior change in the application of hygiene, which is expected to reduce the risk of contamination and improve product quality, thus protecting consumer health and supporting a cleaner and safer snack food industry.